Growth of high quality, high density single-walled carbon nanotube forests on copper foils. (March 2016) - Zhong, Guofang; Yang, Junwei; Sugime, Hisashi; Rao, Rahul; Zhao, Jianwei; Liu, Dameng; Harutyunyan, Avetik; Robertson, John
Abstract: We demonstrate the growth of high quality single-walled carbon nanotube (SWCNT) forests on commercial Cu foils by cold-wall chemical vapor deposition. Time-of-flight secondary ion mass spectrometry was employed to study the effect of annealing on the catalyst evolution with or without an AlOx barrier layer. X-ray photoelectron spectroscopy was used to investigate the chemical states of the catalyst and the barrier layer. SWCNT forests can be reproducibly grown on Cu foils sputter-coated with Al and Fe layers as thin as 6 nm and 0.4 nm, respectively. Al transforms into AlOx on exposure to air and during annealing. Most importantly, such a thin AlOx barrier layer ensures not only the growth of SWCNTs but also an Ohmic contact between the as grown SWCNTs and the Cu base as measured by a two-point probe station. The as-grown SWCNTs exhibit a bimodal distribution of diameters ranging from 0.6 to 4.5 nm, with two peaks centered at 0.8 nn and 2.6 nm, respectively.